The unexpected formation of a mixed bis(η 5-pentamethylcyclopentadienyl)tetracarbonyl(μ 3-ethylidene)triangulotricobalt compound and its structural characterization - Bailey, Webb I.; Cotton, F.Albert; Jamerson, Jackie D. (Journal of organometallic chemistry, 1979)
The title compound was first obtained photolytically from (η 5-Me 5C 5)Co(CO) 2 (by a mechanism not understood) and later by refluxing C 5Me 5H with Co 3(CO) 9CCH 3. It was identified and characterized structurally by X-ray crystallography. The crystals belong to space group P2 1/n with a 9.529(2), b 18.325(4), c 14.801(3) Å, β 95.69(2)° with Z = 4, making one entire molecule the asymmetric unit. Using 2641 reflections with F 0 2 > 3σ (F 0 2 the structure was solved and refined to R 1 = 0.051 and R 2 = 0.067. It consists of a triangular pyramid with two (η 5-C 5Me 5)Co groups and one Co(CO) 3 group in the base and CCH 3 at the apex. The basal edge between the (η 5-C 5Me 5)Co groups has a bridging CO group and a Co—Co distance of 2.405(1) Å, while the other two unbridged Co—Co distances are 2.484(1) and 2.501(1) Å. The distances from the apical C atom to the bridged Co atoms are 1.857(6) and 1.866(6) but 1.932(6) Å to the unique Co atom. The C—C distance in the ethylidyne group is 1.497(9) Å. The structure is closely similar to that of the analogous (η 5-C 5H 5) 2Co 3(CO) 4CCH 3 compound.